INDIAN GUEST COMPLAINT HANDLING STRATEGY THROUGH LEARN METHOD:: A CASE STUDY AT THE OBEROI BEACH RESORT BALI HOTEL - Jasmini, Putu; Andiani, Nyoman Dini; Rahmawati, Putu Indah (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
The rapid increase of Indian tourists in Bali has challenged star-rated hotels to deliver culturally responsive services. This study investigates how Guest Assistants at The Oberoi Beach Resort Bali manage complaints from Indian guests, who often have unique service expectations such as specific dietary preferences, extended family accommodation, and personalized attention. A qualitative descriptive method was employed, combining direct observation, in-depth interviews with the Front Office team, and analysis of internal hotel documentation. The findings reveal several challenges, including cultural misunderstandings, intense communication styles, and high demands for fast and empathetic service. To address these issues, the hotel implements the LEARN method (Listen, Empathize, Apologize, Resolve, Notify), supported by cultural sensitivity training and coordination across departments. Additionally, the use of the OPERA Cloud system allows for efficient documentation and follow-up on complaints, improving response times and personalized guest experiences. The study shows that integrating emotional intelligence, cultural awareness, and technology enhances service quality. As a result, guest satisfaction and loyalty among Indian tourists significantly improve. The implications of this research suggest that culturally adaptive complaint handling strategies are essential in the competitive hospitality industry of Bali. Ultimately, the LEARN-based approach not only resolves immediate issues but also contributes to long-term guest retention and strengthens the hotel's international reputation.